1998
DOI: 10.1038/sj.jhh.1000545
|View full text |Cite
|
Sign up to set email alerts
|

Trough to peak ratio of once-daily lisinopril and twice-daily captopril in patients with essential hypertension

Abstract: The objective of this study was to assess the antihypertensive effect and the trough to peak (T:P) ratio of lisinopril and captopril, in patients with essential hypertension.After 2 weeks of placebo, 69 of 115 eligible patients had office diastolic blood pressure (DBP) between 90 and 114 mm Hg and daytime average DBP above 85 mm Hg during a 25-h ambulatory BP monitoring (ABPM) and were randomised to receive lisinopril (20 mg once daily) or captopril (50 mg twice daily) for 4 weeks. Office and ambulatory BP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Thus, some patients may not get complete 24‐hour BP control with once‐daily lisinopril. Interestingly, previous research using 24‐hour ambulatory BP monitoring has suggested that once‐daily lisinopril dosing is associated with a trough to peak ratio of 0.75, which is generally considered favorable for once‐daily administration of antihypertensives . Whether and to what extent twice‐daily lisinopril dosing improves on this trough to peak ratio is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some patients may not get complete 24‐hour BP control with once‐daily lisinopril. Interestingly, previous research using 24‐hour ambulatory BP monitoring has suggested that once‐daily lisinopril dosing is associated with a trough to peak ratio of 0.75, which is generally considered favorable for once‐daily administration of antihypertensives . Whether and to what extent twice‐daily lisinopril dosing improves on this trough to peak ratio is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Drug therapy is initiated at a low dose to avoid adverse effects. The preferred drugs are long-acting and can be taken only once a day [ 130 ]. Drugs with a high trough/peak ratio (T/P ratio > 0.5) are helpful for improving adherence and to maintain a stable BP with minimal variability [ 131 ].…”
Section: Chapter II Treatment Of Hypertensionmentioning
confidence: 99%
“…Drug therapy is initiated at a low dose to avoid adverse effects. The preferred drugs are long-acting and can be taken only once a day [ 64 ]. Drugs with a high trough/peak ratio (>0.5) are helpful for improving compliance and to maintain a stable BP with minimal variability [ 65 ].…”
Section: Strategies For Prescription Of Antihypertensive Drugsmentioning
confidence: 99%